Assessing the Impact of Financial Characteristics on the Performance of Ghana Club 100 Companies - Arthur-Sam, Jane; Seddighi, Hamid R; Osseo-Asare Jr, Augustus (Technium Business and Management, 2024)
After a decade of reforming policy, building and developing the multi-national market in Ghana, the Ghana Investment Promotion Centre (GIPC) introduced Ghana Club 100 to recognize the top 100 performing companies in terms of their competitiveness and contribution to economic growth. We adopted a quantitative research methodology involving correlational and casual research design to assess the impact of financial characteristics on the performance of 80 listed Ghana Club 100 firms. Financial characteristics represent the independent variables measured using liquidity, financial leverage and business activity, whiles company performance represents measured using return on asset. SPSS Pearson’s correlation coefficient and multiple regression were used to analyze the data gathered from the 80 listed companies. The data analysis reveals four key findings: 1/ a statistically significant positive relationship exists between leverage and performance; 2/ no statistically significant relationship exists between liquidity and performance; 3/ a statistically significant positive relationship exists between business activity and performance; and 4/ leverage, liquidity and business activity had statistically significant positive impact on firm performance. These findings contribute to knowledge by critically explaining the casual relationship between financial characteristics and firm performance with specific reference to Ghana Club 100 companies. The findings have strategic implications for the Ghanaian businesses and economy in terms of enhancing firm’s financial performance. Due to limited access to scarce resources, the scope of the study focused on Club 100 firms which represent all the companies in Ghana. Future research can be conducted on the effect of financial characteristics on the performance of non-listed companies in Ghana.